A Loop-Mediated Isothermal Amplification Assay for the Detection of Treponema pallidum subsp. pertenue - Basing, Laud Anthony W. (Am J Trop Med Hyg, 2020)
The eradication of yaws caused by Treponema pallidum subsp. pertenue is constrained by the lack of rapid, accurate diagnosis. We sought to develop a molecular point-of-care test for the diagnosis of yaws. A loop-mediated isothermal amplification (LAMP) assay with primers targeting the conserved gene, tp0967, with visual detection by lateral flow test strip was developed and optimized. The limit of detection was evaluated while 63 samples from clinical cases of yaws and five samples with polymerase chain reaction (PCR)–confirmed syphilis were used to determine the sensitivity and specificity of the assay compared with the current molecular testing protocol. The developed LAMP assay was found to be optimal when run at 65°C for 30 minutes. The limit of detection from extracted DNA was 2.7 × 10(4) DNA copies/mL. The sensitivity of the LAMP assay using unextracted and DNA extracted samples were 0.67 and 1.00, respectively. None of the syphilis samples tested positive in any of the assays. We show the development of a fast and sensitive LAMP assay for yaws detected by lateral flow test strip. Using extracted DNA, the assay sensitivity is at par with real-time PCR-based detection. The assay can be adapted to minimal sample processing required for infield detection without DNA extraction.